Presence, Behavioural Realism and Performances in Driving Simulation. Issue 19 (2016) - Pallamin, N.; Bossard, C.
Abstract: Driving simulators are increasingly integrated into the training process by driving schools, but doubts still exist concerning the face validity of such tools, in particular concerning accident prevention. To get some enlighten on the usefulness of this training method we investigate which factors are correlated with driving accidents in virtual training. The factors we decide to consider are: 1) the excessive speed, 2) the violation of safety distance 3) the incapability to predict other drivers' behaviour and 4) the perceived "feeling of presence" that often influences the performances in virtual tasks. The results of our study involving 36 participants pointed out that no statistically significant correlation can be established between any of these factors and the number of cars' accidents during the virtual driving task.